QUANTIFICATION OF TOTAL PHENOLIC AND TOTAL FLAVONOID CONTENT OF EXTRACTS OF TAGETES ERECTA FLOWERS - N, Siddhu; J, Saxena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Tagetes erecta, marigold, has various ethnomedicinal uses. It has a wide variety of bioactive components such as polyphenols and flavonoids which show different bioactivities. The aim of the present study is to quantitatively estimate total phenolic content (TPC) and total flavonoid content (TFC) of different extracts of T. erecta flowers. Methods: Extraction was done by maceration process, sequentially from non-polar to polar. Chloroform, ethyl acetate, and methanol extracts of T. erecta flowers were subjected to preliminary phytochemical screening. The extracts were analyzed for TPC and TFC using gallic acid and rutin as standard, respectively. Result: Phytochemical screening of different extracts showed the presence of carbohydrates, flavonoids, phenolics, fats, and oils. TPC and TFC in extracts of T. erecta varies with solvents. The study revealed that methanolic extract possesses the highest phenolic content, 49.76Â±0.29 mg gallic acid equivalents/g extract, and also maximum flavonoid content, 13.43Â±0.43 mg RE/g extract, among the three extracts. Conclusion: Higher value of phenolics and flavonoid indicates higher antioxidant activity. The present study revealed that methanolic extract has the highest phenolic and flavonoid content. This indicates that the flowers may possess a good antioxidant property and further research could be carried out.